Triceps skinfold–albumin index significantly predicts the prognosis of cancer cachexia: A multicentre cohort study. Issue 1 (25th December 2022) - Yin, Liangyu; Cui, Jiuwei; Lin, Xin; Li, Long; Li, Na; Fan, Yang; Zhang, Ling; Liu, Jie; Chong, Feifei; Lu, Zongliang; Wang, Chang; Liang, Tingting; et al.
Abstract: Background: The fat mass and nutritional status play important roles in the onset and progression of cancer cachexia. The present study evaluated the joint prognostic value of the fat mass, as indicated by the triceps skinfold thickness (TSF), and the serum albumin level, for mortality in patients with cancer cachexia. Methods: We performed a multicentre cohort study including 5134 patients with cancer cachexia from January 2013 to April 2019. The sum of the TSF (mm) and serum albumin (g/L) was defined as the triceps skinfold–albumin index (TA). Harrell's C index, a time‐dependent receiver operating characteristic (ROC) curve analysis and the area under the curve (AUC) were used to evaluate the prognostic performance of the TA and other indices. Optimal stratification was used to identify the thresholds to define a low TA, and the association of the TA with all‐cause mortality was evaluated using Kaplan–Meier analysis and Cox proportional hazard regression models. Results: The study enrolled 2408 women and 2726 men with a median age of 58.6 years and a median follow‐up of 44 months. A total of 607 women (TA < 49.9) and 817 men (TA < 45.6) were classified as having a low TA. The TA showed better discrimination performance ( C index = 0.621, 95% confidence interval [CI] = 0.607–0.636) to predict mortality in patients with cancer cachexia than the handgrip strength, the nutritional risk index, the prognostic nutritional index, the controlling nutritional status index, the systemic immune‐inflammation index, the modified Glasgow prognostic score, and the TSF or albumin alone in the study population (all P < 0.05). The 1‐, 3‐ and 5‐year time‐dependent ROC analyses (AUC = 0.647, 0.625 and 0.630, respectively) showed that the TA had the highest prognostic value among all indices investigated (all P < 0.05). Univariate analysis showed that a lower TA was associated with an increased death hazard (hazard ratio [HR] = 1.859, 95% CI = 1.677–2.062), regardless of the sex and cancer type. Multivariable survival analysis showed that a lower TA was independently associated with an increased death hazard (HR = 1.381, 95% CI = 1.223–1.560). This association was significantly strengthened in patients who did not receive curative chemotherapy (HR = 1.491, 95% CI = 1.298–1.713), those who had higher serum total protein levels (HR = 1.469, 95% CI = 1.284–1.681) and those with better physical performance (HR = 1.453, 95% CI = 1.271–1.662). Conclusions: This study defined and evaluated a new prognostic index, the TA, which may improve the selection of intervention strategies to optimize the survival of patients with cancer cachexia.